Interaction and sedimentary process between the evolution of the bar and bifurcation of the river in the far-source fine-grained braided river: Numerical simulation analysis inspired by modern deposition - Quan Gan (地质科技通报, 2021)
The far-source fine-grained braided river is widely distributed in the middle and lower reaches of the river.The tight oil and gas reservoir formed by the far-source fine-grained braided river is hard for further exploration of potential oil and gas.Combined with the remote sensing image of the modern far-source fine-grained braided river, the growth and evolution process of the far-source fine-grained braided river was modeled by the numerical simulation software Delft3D based on sediment hydrodynamics.The influences of the river discharge and the supply of mud and sand on the morphology of the far-source fine-grained braided river are simulated.The interaction and sedimentary process between the evolution of the bar and the bifurcation of the river in the far-source fine-grained braided river are analyzed and verified.The main findings are as follows:①The widening of the channel along the downstream direction is the main topographic condition that triggers the formation of the far-source fine-grained braided river.The flow velocity and bank firmness are important factors to determine the river width.②The interaction and sedimentary process between the evolution of the bar and bifurcation of the river in the far-source fine-grained braided river are a sedimentary evolution process of the interaction between the sediment of the bar and the flowing water of the river.The interaction between the sediment of the bar and the flowing water of the river includes deposition of sediment in the river and erosion of sediment by the river.③The aggradation of the bar in the river, the separation of the bar and bank, and the river avulsion are the three main forms of the interaction and sedimentary process between the evolution of the bar and the bifurcation of the river in the far-source fine-grained braided river.This paper enriches the theory of sedimentation of the far-source fine-grained braided river.This study is helpful to analyze the spatial distribution of reservoirs in the far-source fine-grained braided river sedimentary facies and to apply it to the in-depth exploration and development of oil and gas.